Bound Ca2+ moves faster and farther from single open channels than free Ca2+ - Mironov, S. L. (Frontiers in Physiology, 2023)
A concept of Ca 2+ nanodomains established in the cytoplasm after opening single calcium channels helps to mechanistically understand the physiological mechanisms of Ca 2+ signaling. It predicts standing gradients of cytoplasmic free Ca 2+ around single channels in the plasma membrane. The fate of bound Ca 2+ attracted much less attention. This study aimed to examine the profiles of Ca 2+ bound to low-mobility buffer such as bulky Ca 2+ -binding proteins. Solution of non-linear PDEs for an immobile buffer predicts fast decay of free [Ca 2+ ] from the channel lumen and the traveling wave for bound Ca 2+ . For low-mobility buffer like calmodulin the calculated profiles of free and bound Ca 2+ are similar. Theoretical predictions are tested by imaging 1D profiles of Ca 2+ bound to low-mobility fluo-4-dextran. The travelling waves of bound Ca 2+ are observed that develop during opening of single channel. The findings tempt to propose that Ca 2+ signaling may not be solely related by the absolute free [Ca 2+ ] at the sensor location, which is extremely localized, but determined by the time when a wave of bound Ca 2+ reaches a threshold needed for sensor activation.